Design of Mine-used Substation with High Reliability - ZHU Qian-wei; LIU Chun-xia (Gong-kuang zidonghua, 2011)
Most mine-used substations use analog signal transmission mode to communicate with sensors. The transmission mode is easily influenced by electromagnetic interference of coal mine underground, which would reduce stability and reliability of safety monitoring and control system of coal mine. To solve the problem, a mine-used substation with high reliability was designed which uses digital transmission mode to communicate with sensors. Structure and design of hardware and software of the substation were introduced in details. The test result showed that the substation passed anti-interference performance test regulated by AQ 6201-2006 General Specification of Safety Monitoring and Control System of Coal Mine and has higher stability.